Bone Bruise Distribution Patterns After Acute Anterior Cruciate Ligament Ruptures: Implications for the Injury Mechanism. Issue 4 (15th April 2020) - Shi, Huijuan; Ding, Li; Jiang, Yanfang; Zhang, Haocheng; Ren, Shuang; Hu, Xiaoqing; Liu, Zhenlong; Huang, Hongshi; Ao, Yingfang
Background: Bone bruises observed on magnetic resonance imaging (MRI) after an anterior cruciate ligament (ACL) injury could provide significant information about ACL injury mechanisms. Purpose/Hypothesis: The purpose of this study was to investigate common bone bruise patterns after an ACL injury. It was hypothesized that the most common bone bruise distribution pattern would be only the lateral side of both the femur and tibia. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Knee MRI scans of patients who underwent acute ACL reconstruction from August 2016 to August 2018 at our institution were selected. Imaging sequences in the sagittal and coronal planes were used for determining the bone bruise location in the lateral-medial and anterior-posterior directions, respectively. The presence, location, and intensity of bone bruises within specific compartments of the tibia and femur were documented. The relative bone bruise patterns of the tibia and femur were classified and analyzed. Results: A total of 207 patients (165 men, 42 women) met the inclusion criteria from a total of 4209 ACL reconstruction cases. The most common relative bone bruise pattern was located on only the lateral side of both the femur and the tibia (44.4%), followed by the lateral and medial sides of both the femur and tibia (29.0%). For the pattern found on the lateral and medial sides of both the femur and tibia, the bone bruises on only the lateral side of both the tibia and femur were more severe ( P < .001 and P < .001, respectively) and more anterior ( P < .001 and P < .001, respectively) than those on only the medial side. Conclusion: The most common relative bone bruise pattern observed was on only the lateral side of both the tibia and femur. Bone bruises on the lateral side were more severe than those on the medial side in patients with bone bruises on the lateral and medial sides of both the femur and tibia. Anterior translation of the tibia relative to the femur occurred during an ACL injury based on the location of bone bruises in the anterior-posterior direction.